OUTLINE OF A MECHANISM FOR THE EMERGENCE OF SAN LUIS POTOSIIRAL ARMS FROM THE NUCLEUS OF A GALAXY - PISMIS, P (UNAM, Observatorio Astronómico Nacional, CD MEXICO, DF, MEX, 1967)
This article attempts to account for the symmetrical emergence of spiral arms. The observed non-thermal component of the radio source occupying the very center of the Galaxy suggests strongly that this region is the seat of a magnetic field and of high en
BOL OBS TONAN TACUB
Keywords: OUTLINE, MECHANISM, EMERGENCE, SPIRAL ARMS, NUCLEUS, GALAXY; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; GALAXIAS